A new species of soft-winged flower beetles of the genus Kuatunia Evers, 1945–48 (Coleoptera, Cleroidea, Malachiidae) from Nepal - Tshernyshev, Sergei E. (Zootaxa, 2015)
A new malachiid species of the genus Kuatunia Evers is described: K. matthiasi sp. n., from Nepal, Seti Province; figures of male habitus, elytral appendices, genitalia, and a distribution map are presented. A determination key to all species of Kuatunia is also proposed.